Isolation of human pluripotent stem cell-derived sensory neuron subtypes by immunopanning - Saito-Diaz, Kenyi; James, Christina; Patel, Archie Jayesh; Zeltner, Nadja (Frontiers in Cell and Developmental Biology, 2023)
Sensory neurons (SNs) detect a wide range of information from the body and the environment that is critical for homeostasis. There are three main subtypes of SNs: nociceptors, mechanoreceptors, and proprioceptors, which express different membrane proteins, such as TRKA, TKB, or TRKC, respectively. Human pluripotent stem cell technology provides an ideal platform to study development and diseases of SNs, however there is not a viable method to isolate individual SN subtype for downstream analysis available. Here, we employ the method immunopanning to isolate each SN subtype. This method is very gentle and allows proper survival after the isolation. We use antibodies against TRKA, TRKB, and TRKC to isolate nociceptors, mechanoreceptors, and proprioceptors, respectively. We show that our cultures are enriched for each subtype and express their respective subtype markers. Furthermore, we show that the immunopanned SNs are electrically active and respond to specific stimuli. Thus, our method can be used to purify viable neuronal subtypes using respective membrane proteins for downstream studies.